Бимодальные технологии получения полиэтилена 3-го поколения (обзор) - Лебедев, Владимир Владимирович (НТУ "ХПИ", 2011)
In paper the survey concerning reception of third generation polyolefins – bimodal polyethylenes is made. The basic licensed technologies of reception of bimodal polyethylenes on one-and two-reactor to circuit designs is resulted, features of their synthesis are observed. Their key properties and ranges of application are characterised
Keywords: термопласты; молекулярная масса; физико-механические свойства; однореакторная газофазная технология